DETERMINATION OF RECYCLING OPINIONS OF PRESERVICE SCIENCE TEACHERS - Mustafa UZOĞLU (Fırat University, 2020)
Human, while continuing its vital activities interacts with the environment. These activities have negative effects on the environment. Environmental pollution is the most important of these adverse effects. According to the national literature, environmental pollution has increased, limited resources are almost exhibited. As measure against increasing environmental pollution, the concept of recycling and people's information has become important. So, in this study, the opinions of science teachers will be asked about recycling. In this study, a survey was conducted. The study was conducted according to the descriptive method. 55 science teachers participated in the survey in 2016-2017 educational year in Giresun City. Theese surveys evaluated by content analysis method. At the end of the review, teachers' views on recycling presented in tabular form. By examining the data obtained, it was found that teachers' information about recycling was sufficient but they did not take sufficient responsibility for recycling.